DYNAMIC CHANGES IN THE CELLULAR COMPOSITION IN THE UROPSAMMUS OF ARTIFACTUAL BLADDER - Savchuk, R.V.; Kostyev, F.I.; Vit, V.V. (World of Medicine and Biology, 2020)
The purpose of the work was to evaluate the dynamic changes in the cellular composition of the artifactal bladder uropsammus. The dynamics of structural changes in the urine sediment after surgery was revealed, which indicates that, in the presence of positive clinical results after the operation, the processes of restructuring the epithelial lining of the intestinal fragment transplanted instead of the bladder, aimed at performing other functions, are being completed. Based on the data obtained, it is possible to use a cytological study in the clinic to establish the dynamics of the process after surgical treatment, to determine the degree of epithelium exfoliation in the transplanted intestine, as well as to correct individual links of the adaptation process under the new conditions of the transplanted intestinal fragment functioning, which are fundamentally different.
Keywords: artifactual bladder; cell composition; adaptation